Game Theory in Signal Processing and Communications. (19th November 2009) - Boche Boche, Holger Holger; Han Han, Zhu Zhu; Larsson Larsson, Erik G. Erik G.; Jorswieck Jorswieck, Eduard A. Eduard A.
Abstract :